Protein Structure-Based Design of Novel Semisynthetic Metallotrypsin - Misran, Azizah (2006)
A detailed study of the surface region trypsin from bovine pancreas was performed to gain insight into its biological functions and interactions that helped to determine the binding specificity. Twenty four pockets were identified in trypsin from Protein Data Bank (PDB) file entry 1AUJ using Computed Atlas of Surface Topography of proteins (CASTp). Nevertheless, only five biggest pocket cavities were selected; pocket 20, 21, 22, 23, and 24 since those pocket cavities would provide insight of location where ligand could bind as well as to identify the cavities that can aid in diffusion of the ligands. It also offered the identification of surface features and functional region of protein. Analyses of volume, surface area, and amino acids that participated in each pocket cavity were also determined. Systematic molecular docking studies using AutoDock 3.0.5 was performed on the five largest pocket cavities in trypsin. A set of ten chemical ligands was docked onto five biggest pocket cavities. The results showed that the biggest rigid ligand 1,10-phenanthroline (PHN) preferred to bind at pocket 24 as indicated by the lowest docked energy value (-8.74 kcal/mol). Systematic analyses on molecular docking for various metal ions such as Fe2+, Mg2+, Ca2+, and Zn2+ to the protein ligand complex showed almost similar docked energy at all pocket cavities. Docking results of trypsin-PHN complex showed that the lowest docked energy of -9.63 kcal/mol for Fe2+ at pocket cavity 21, followed by Mg2+ (-7.00 kcal/mol) at pocket 23, Ca2+ (-5.56 kcal/mol) and the highest docked energy value that was Zn2+ with -0.02 kcal/mol at the pocket cavity 21. Experimental studies have focused on PHN as an intermediate ligand since PHN was a bidentate ligand that provides more sites for interactions which capable of generating stable complex. It was found that at concentration 100 μM of PHN increased the activity of trypsin by 40 % higher than native trypsin. However, analysis among the metal ions on trypsin-PHN complex indicated that Ca2+ was the only metal ions capable of enhancing the activity of trypsin about 10 % than native trypsin at the concentration of 5 μM.